Advances in potato chemistry and technology - Singh, Jaspreet (Food scientist); Kaur, Lovedeep (Academic Press, 2016)
Advances in Potato Chemistry and Technology, Second Edition, presents the latest knowledge on potato chemistry, including the identification, analysis, and uses of chemical components in potatoes. Beginning with a brief description of potato components, the book then delves into their role during processing, then presenting information on strategies for quality optimization that provides students, researchers, and technologists working in the area of food science with recent information and updates on state-of-the-art technologies. The updated edition includes the latest information related to the identification, analysis, and use of chemical components of potatoes, carbohydrate and non-carbohydrate composition, cell wall chemistry, an analysis of glycoalkaloids, phenolics and anthocyanins, thermal processing, and quality optimization. In addition, new and sophisticated methods of quality determination of potatoes and their products, innovative and healthy potato-based foods, the future of genetically modified potatoes, and the non-food use of potatoes and their products is discussed.